Telomere length and its relationships with lifestyle and behavioural factors: variations by sex and race/ethnicity. (1st October 2020) - Vyas, Chirag M; Ogata, Soshiro; Reynolds, Charles F; Mischoulon, David; Chang, Grace; Cook, Nancy R; Manson, JoAnn E; Crous-Bou, Marta; De Vivo, Immaculata; Okereke, Olivia I
Abstract: Background: Adherence to healthy lifestyles/behaviours promotes healthy ageing. However, little is known about whether age, sex and/or race/ethnicity moderate associations of lifestyle/behavioural factors with relative telomere length (RTL), a potential biomarker of ageing. Methods: We included 749 midlife to older non-Hispanic White ( n = 254), Black ( n = 248) and Hispanic ( n = 247) US participants [mean (standard deviation) age = 69.3 (7.2) years; women: 50.5%]. We extracted genomic DNA from peripheral leucocytes. RTL was assayed using real-time quantitative polymerase chain reaction. Multivariable regression was used to examine associations between lifestyle/behavioural exposures (i.e. physical activity, alcohol consumption, smoking and depression) with RTL. Results: Increasing chronological age was associated with shorter RTL ( P < 0.01). Higher physical activity was associated with longer RTL ( P -trend = 0.03); daily versus never/rare alcohol consumption and 30+ versus <5 smoking pack-year were associated with shorter RTLs ( P -trend = 0.02). Associations varied significantly by sex and race/ethnicity. The association between physical activity and longer RTL appeared strongest among non-Hispanic Whites ( P -interaction = 0.01). Compared to men, women had stronger associations between heavy smoking and shorter RTLs ( P -interaction = 0.03). Light/moderate alcohol consumption (monthly/weekly) was associated with longer RTL among non-Hispanic Whites, while daily consumption was related to shorter RTLs among Blacks and Hispanics ( P -interactions < 0.01). Associations of daily alcohol and heavy smoking with shorter RTLs were particularly apparent among Black women. Conclusion: We observed novel variations by sex and race/ethnicity in associations between lifestyle/behavioural factors and RTL. Further work is needed to replicate these findings and to address potential public health implications for modifying strategies by sex or across racial/ethnic groups to optimise lifestyles/behaviours for healthy ageing.